2009
DOI: 10.1097/sla.0b013e31818b73dc
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Different Crystalloid Volume Regimes on Intestinal Anastomotic Stability

Abstract: We could demonstrate for the first time in a systematic investigation, that the quantity of crystalloid infusion, applied intraoperatively, has a significant impact on functional (bursting pressure) and structural (hydroxyproline) stability of intestinal anastomoses in the early postoperative period. Because the stability and quality of an intestinal anastomosis have an impact on insufficiency rates, it should be noted that volume overload may have deleterious effects on anastomotic healing and postoperative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(80 citation statements)
references
References 25 publications
2
74
0
2
Order By: Relevance
“…27,28 It is postulated that increased fluid volumes can cause tissue oedema thereby reducing anastomotic strength. 29 This is particularly important in rectal cancer surgery as anastomotic leakage is associated with poor outcomes. 23,30 Our study found that anastomotic leaks were more common in the group that received more than 3500ml but this was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 It is postulated that increased fluid volumes can cause tissue oedema thereby reducing anastomotic strength. 29 This is particularly important in rectal cancer surgery as anastomotic leakage is associated with poor outcomes. 23,30 Our study found that anastomotic leaks were more common in the group that received more than 3500ml but this was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…2 Furthermore, a study in rats undergoing a bowel resection and anastomosis showed that excessive crystalloid results in submucosal intestinal edema, lower anastomotic bursting pressure, and a decrease in the structural stability of intestinal anastomoses in the early postoperative period. 20 Maintenance fluid requirements during surgery can be delivered with a 1-3 mLÁkg -1Áhr -1 infusion of a balanced crystalloid solution. 19,21 The aim should be to maintain preoperative body weight.…”
Section: Maintenance Fluid Therapymentioning
confidence: 99%
“…9% saline. Nevertheless, a study in rats undergoing small-bowel resection and anastomosis has shown that an excess of even a balanced crystalloid can result in submucosal intestinal oedema, a decrease in anastomotic bursting pressure and a decrease in hydroxyproline concentration in the anastomotic region, implying impairment of collagen synthesis and wound healing (48) .…”
Section: Study or Subgroupmentioning
confidence: 99%